Medical identifier technology for pilgrims during the Hajj season - Ibrahim, N.J.; Mohd Yakub, N.M.; Mohd Yusoff, Mohd Yakub @ Zulkifli; Husin, M.; Idris, Mohd Yamani Idna; Abdul Rahman, N.N. (2012)
Hajj is known as one of the Muslim’s ritual duties as described in the Five Pillar of Islam. Since many people gather in one place, it tends to create many problems, especially in crowded environment, such as flood, fire and stampedes. It is not included with died pilgrims that always happen every year, because of age factor and unfortunate incident, as well as lost pilgrims that always been reported each hour during Hajj. Without papers that showing their exact location as well as contact number, yet with the problems of communication (language barriers), always puts a tremendous pressure on the security officers who taking care of pilgrims. This paper seeks to provide a comprehensive review about the potential technology and design which suitable to be implemented as a medical identifier. This medical device will be built into a new design of bracelet, due to be worn by pilgrims. This proposed bracelet is specifically designated for them, due to replace the existing bracelet worn by pilgrims as identification tag. It is equipped with additional function of technology, which capable to monitor the pilgrim’s health condition, as well as pilgrims’ data information.